Unconditional IMF Financial Support and Investor Moral Hazard - Kim, Jun. (Washington, D.C. : International Monetary Fund, 2007)
This paper develops a simple model of international lending, and calibrates it to assess quantitatively the effects of contingent IMF financial support on the risk premiums and the crisis probability. In the model, the country borrows in both short and long term; market (coordination) failure triggers a liquidity run and inefficient default; and the IMF lends unconditionally under a preferred creditor status. The model shows that IMF financial support can help prevent a liquidity crisis without causing investor moral hazard by helping to remove a distortion-effectively subsidizing ex post short-term investors (who run for the exit) at the expense of long-term investors (who are locked in). The resulting equilibrium is welfare enhancing as both the country's borrowing costs and the likelihood of a crisis are lower. The calibration exercises suggest that IMF-induced investor moral hazard-which occurs if the IMF lends at a subsidized rate-is unlikely to be a concern in practice, particularly if the country's economic fundamentals are strong and short-term debt is small.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet